Revampment of surface permanent magnet synchronous motor design for ameliorated torque profile in e‐mobility applications - Anshul K. Mishra; Bharat S. Rajpurohit; Rajeev Kumar (IET Electrical Systems in Transportation)
Abstract High‐frequency audible noise and high‐frequency vibrations (HFVs) in electrical vehicles are primarily caused by vibrations and ripples generated in the traction motor. The appositeness of permanent magnet synchronous motors (PMSMs) has been boosting in traction applications due to their high energy density, compact size and high torque to weight ratio. A novel and step‐by‐step design of medium power, high speed, surface PMSM, suitable for e‐bus or e‐truck applications, with suppressed torque ripples, is presented. Initially, a conventional machine design approach has been used to design 100 kW PMSM. In the next step, the design has been ameliorated by making it a fractional slot winding machine to suppress the winding harmonics. Finally, the effect of the permanent magnet embrace size on the torque ripple has been investigated. A nonlinear relationship between the torque ripple and PMSM magnetic embrace has been developed. The developed relationship has been validated in the finite element model of the machine. Gradient‐based nonlinear sequential programming has been used to find out the optimum magnetic embrace for the minimised torque ripple. The effectiveness of the optimised design has been revalidated in the FE software. The step‐by‐step design process described here can reduce the torque ripple by 85% of optimised design compared to the conventionally designed PMSM.